Estudantes surdos e os núcleos de acessibilidades nas instituições federais de ensino superior do Triângulo Mineiro de 2010-2020 - CASTRO, ADRIANA CRISTINA DE (2023)
This dissertation is enrolled in the Postgraduate Program in Education linked to the State, Policy and Management of Education line. This is a qualitative field research, and in its macro context it investigates the implementation and/or restructuring of Accessibility Centers (NAs) in Federal Higher Education Institutions (IFES), with the financial support of the Include Program. The aspect chosen for this study has the following development: how did the Federal Higher Education Institutions of the Triângulo Mineiro offer accessibility support to deaf students in the period between 2010 and 2020? The hypothesis for this question is that the Incluir Program contributed significantly to the implementation or restructuring of NAs in the Triângulo Mineiro, meeting the learning needs of deaf students in higher education. Given this, the general objective is to understand how these IFES organized Special Education services through the NAS and whether they managed to improve access, retention and completion of deaf students in the proposed section. To this end, the specific objectives sought to: discuss public educational policies for the inclusion of deaf students in higher education; map the years of entry and completion of your studies; check which institutions have increased access for deaf students; identify and analyze the Special Education services that NAs offered to these students. The documentary review had theoretical support from “Deaf Studies”, supported by authors such as Gladis (1998); Perlin (2004); Quadros (2006); Sá (2006); Rocha (2007); Skliar (2008); Strobel (2008); Lacerda (2010); Thoma (2002, 2010, 2016) and Kraemer (2011). Data collection was carried out using the quantitative analysis Survey. In this way, a questionnaire was prepared and later sent, by email, to the coordinators of the IFES of the Triângulo Mineiro: the Federal Institute of Triângulo Mineiro (IFTM), Patos de Minas campus, the Federal University of Triângulo Mineiro (UFTM), Uberaba campus, and the Federal University of Uberlândia (UFU), Uberlândia campus. The results obtained were analyzed through the theoretical lens of Deaf Studies, and Foucauldian governmentality and biopower. Given this context, we found that between 2010-2020, 21 deaf students were enrolled in higher education courses offered by these institutions. Of these, 66.7% entered through ENEM. Based on the results obtained, there was an increase in deaf entrants assisted by NAs implemented or restructured by financial subsidies from the Incluir Program, this is the so-called explicit discourse. However, there is a subliminal discourse present in legal documents, suggesting that individuals are responsible for their schooling. Thus, the deaf person is seen as an entrepreneur of himself, incorporating Foucault's concept of economic man, in his ability and participation to play the game of inclusion, whose intervention by the laissez faire State is responsible for formulating public policies to maintain this system. In this sense, deaf students, even reaching higher levels of education, have their subjectivity captured and shaped by the market. This view is refuted by the field of Deaf Studies, which conceives the deaf as an emancipated subject, militant of their educational, linguistic, identity and cultural rights. In this case, deafness is conceived as a political difference and not as a pathology.